Volatile emissions of watercress (Nasturtium officinale) leaves and passion fruit (Passiflora edulis) seeds against Meloidogyne incognita. Issue 4 (20th November 2019) - Silva, Marcela F; Campos, Vicente P; Barros, Aline F; Terra, Willian C; Pedroso, Márcio P; Gomes, Vanessa A; Ribeiro, Clerio R; Silva, Fabíola J
Abstract : Watercress leaf and passion fruit seed macerates produce volatile organic compounds toxic to Meloidogyne incognita and 1‐octanol, found in volatile emissions of watercress leaves, shows nematicidal activity against M. incognita . Abstract: BACKGROUND: Plants emit volatile organic compounds (VOCs) with several functions, including toxicity to plant‐parasitic nematodes (PPNs). However, the toxicity of VOCs from watercress leaves ( Nasturtium officinale ) and passion fruit seeds ( Passiflora edulis ) against PPNs has not yet been studied. RESULTS: Biofumigation with watercress leaves and passion fruit seeds reduced the infectivity and reproduction of Meloidogyne incognita in tomato plants. The VOCs emitted by watercress leaves and passion fruit seeds caused immobility of M. incognita second‐stage juveniles (J2 ). The reduction in infectivity and reproduction of M. incognita reached 89% and 99%, respectively, when J2 were exposed to watercress VOCs. Additionally, water exposed to VOCs emitted by watercress caused 79% M. incognita J2 mortality. The volatilome of the toxic water contained 12 compounds, mainly alcohols. The emissions from watercress leaves and passion fruit seeds contained 26 and 12 compounds, respectively, according to gas chromatography–mass spectrometry analysis. The 1‐octanol occurring in watercress emissions demonstrated in vitro and in vivo nematicidal activity against M. incognita, with a lethal dose necessary to cause 50% mortality (LC50 ) of 382.5 μg mL −1 . CONCLUSIONS: Watercress leaf and passion fruit seed macerates emitted VOCs with nematicidal activity against M. incognita . The compound 1‐octanol identified in watercress emissions may be useful for the nematicide‐producing industry. © 2019 Society of Chemical Industry